LO95: A prospective evaluation of mild traumatic brain injuries in a working population in Edmonton, AB. (15th May 2017) - Gaudet, L.; Eliyahu, L.; Lowes, J.; Beach, J.; Mrazik, M.; Cummings, G.; Latoszek, K.; Carroll, L.; Holroyd, B.R.; Rowe, B.H.
Abstract : Introduction: Patients with mild traumatic brain injury (mTBI) frequently present to the emergency department (ED); however, wide variation in diagnosis and management has been demonstrated in this setting. Sub-optimal mTBI management can contribute to post-concussion syndrome (PCS), affecting vocational outcomes like return to work. This study documented the work-related events, ED management, discharge advice, and outcomes for employed patients presenting to the ED with mTBI.Methods: Adult (>17 years) patients presenting to one of three urban EDs in Edmonton, Alberta with Glasgow coma scale score ≥13 within 72 hours of a concussive event were recruited by on-site research assistants. Follow-up calls ascertained outcomes, including symptoms and their severity, advice received in the ED, and adherence to discharge instructions, at 30 and 90 days after ED discharge. Dichotomous variables were analyzed using chi-square testing; continuous variables were compared using t-tests or Mann-Whitney tests, as appropriate. Work-related injury and return to work outcomes were modelled using logistic or linear regression, as appropriate.Results: Overall, 250 patents were enrolled; 172 (69%) were employed at the time of their injury and completed at least one follow-up. The median age was 37 years (interquartile range [IQR]: 24, 49.5), both sexes were equally represented (48% male), and work-related concussions were uncommon (16%). Work-related concussion was related to manual labor jobs and self-reported history of attention deficit disorder. Patients often received advice to avoid sports (81%) and/or work (71%); however, the duration of recommended time off varied. Most employed patients (80%) missed at least one day of work (median=7 days; IQR: 3, 14); 91% of employees returned to work by 90 days, despite 41% reporting persistent symptoms. Increased days of missed work were linked to divorce, history of sleep disorder, and physician's advice to avoid work.Conclusion: While work-related concussions are uncommon, most employees who sustain a mTBI at any time miss some work. Many patients experience mTBI symptoms past 90 days, which has serious implications for workers' abilities to fulfill their work duties and risk of subsequent injury. Workers, employers, and the workers compensation system should take the necessary precautions to ensure that workers return to work safely and successfully following a concussion.